Reply to the Letter to the Editor from Dr. Seet-Lee and Colleagues - Esteves, Mário; Monteiro, Mariana P.; Duarte, José Alberto (International Journal of Sports Medicine, 2022)
The authors would like to thank Dr. Seet-Lee and colleagues for their comments on our recently-published manuscript in the International Journal of Sports Medicine 1. Dr. Seet-Lee and colleagues highlighted some inadequacies, specifically when using mean difference or raw mean difference as effect measure. However, when evaluating blood vessel density by different reliable and validated histological procedures, would it be wrong to assume, as we did, that all the obtained measurements from different staining always vary equally, directly and linearly, with the actual parameter under study? Are Dr. Seet-Lee and colleagues assuming that the results of histological observations of blood vessels, marked with different techniques and stains, are neither compatible nor governed by the same measurement scales? We regret, but we are firmly convinced that we proceeded properly. Moreover, we should not assume that standardized effect sizes will make comparisons meaningful 2. Particularly, as the standardized mean difference indicates the difference before and after the intervention in terms of standard deviations instead of actual scores, it assumes that different outcome scales are linear transformation of each other and the standard deviation (SD) is equal across all studies 3.